Hymenocallis littoralis ameliorates inflammatory responses in LPS-stimulated RAW264.7 cells and HCl/EtOH-induced gastric mucosal injury via targeting the MAPK pathway. (15th September 2022) - Zhang, Jianmei; Sayakoummane, Sousath; Kim, Soo Ah; Lee, Jong Sub; Choung, Eui Su; Kim, Eun Sil; Lee, Seung-Gyu; Yum, Jinwhoa; Lee, Byoung-Hee; Lee, Sarah; Kim, Ji Hye; Cho, Jae Youl
Abstract: Ethnopharmacological relevance: Hymenocallis littoralis (Jacq.) Salisb. Also known as Pancratium littorale Jacq. And Hymenocallis panamensis Lindl., is a medicinal plant from the family Amarylideceae used for emetic and wound healing and has manifested anti-neoplastic, anti-oxidant, and anti-viral properties. Aim of the study: The aim of this paper is to investigate the anti-inflammatory potential and molecular mechanism of H. littoralis against lipopolysaccharide (LPS)-induced macrophages and in vivo HCl/EtOH-induced gastritis mucosal injury models. Materials and methods: The production of pro-inflammatory cytokines and mediators was evaluated by Griess assay, RT-PCR, and real-time PCR. Moreover, the relevant proteins of mitogen-activated protein kinases (MAPKs) including ERK, JNK, p38, c-Jun, and c-Fos were detected using immunoblotting. Results: We demonstrated that H. littoralis prominently dampened production of nitric oxide (NO) in LPS-, poly I:C-, or pam3CSK-stimulated RAW264.7 cells; down-regulated the expression levels of interleukin 6 (IL-6) and inducible nitric oxide synthase; and markedly attenuated the luciferase activities of AP-1 reporter promoters. Moreover, H. littoralis administration prominently downregulated c-Fos and c-Jun phosphorylation as well as JNK1, ERK2, and MKK7 overexpression in HEK 293T cells. Furthermore, H. littoralis displayed anti-inflammatory effects in the HCl/EtOH-induced gastritis mice model. Conclusions: Cumulatively, these results demonstrated that H. littoralis exerts eminently anti-inflammatory activities in LPS-stimulated RAW264.7 cells in vitro and in HCl/EtOH-induced gastritis mice models in vivo . These activities could be attributed to its modulatory effects on the MAPK signaling pathway. Graphical abstract: Image 1 Highlights: Hymenocallis littoralis ethanol extract (Hl-EE) is able to mediate the inflammatory response. Hl-EE downregulates the expression levels of iNOS and IL-6 at the transcriptional level. Hl-EE exerts eminently anti-inflammatory activities through targeting ERK/JNK in the MAPK signaling pathway. Hl-EE exhibits extremely strong efficacy in HCl/EtOH gastritis model in vivo.